Two-step esterification of palm fatty acid distillate in ethyl ester production: Optimization and sensitivity analysis. (April 2018) - Kanjaikaew, Utaiwan; Tongurai, Chakrit; Chongkhong, Sininart; Prasertsit, Kulchanat
Abstract: Low-cost palm fatty acid distillate (PFAD) feedstock to produce biodiesel is of interest. Single step esterification of PFAD is effective but requires large amounts of chemicals. Removal of water in a two-step process increases the effectiveness of FFA conversion with methanol, but ethanol has yet to be investigated and hence was proposed. Effects of parameters: ethanol to FFA molar ratio, temperature, time and catalyst amount, were investigated. In the first step, catalyst amount was kept constant; and for the second-step, the reaction temperature was fixed. RSM coupled with sensitivity analysis enabled parameters to be optimized. Optimal conditions for the first step were: 4:1 M ratio, 353 K and 15 min, resulting in 88% FFA conversion. In the second step, the conversion reached 86.8% under these conditions: 27:1 M ratio, 53 min and 35.3 wt% catalyst amount. Under these two sets of optimal conditions, the overall FFA conversion of 98.44% was comparable to other studies. The attempt on the use of ethanol to produce ethyl ester in a two-step process of PFAD is quite successful: ethanol, renewable and more environmental friendly, is a contending effective alternative. Highlights: Ethanol was investigated in two-step esterification of PFAD. FFA conversion was 98.44% under mild condition; comparable with many other studies. Ethyl ester was produced using less reagent in a self-reliant technology. Improved operation conditions result from dewatering in first-step esterification. Ethanol is proven an effective alternative in two-step FFA conversion.